Chronic noncancer pain is not associated with accelerated brain aging as assessed by structural magnetic resonance imaging in patients treated in specialized outpatient clinics. Issue 3 (March 2020) - Sörös, Peter; Bantel, Carsten
Abstract : Abstract: Chronic pain is often associated with changes in brain structure and function, and also cognitive deficits. It has been noted that these chronic pain-related alterations may resemble changes found in healthy aging, and thus may represent accelerated or premature aging of the brain. Here, we test the hypothesis that patients with chronic noncancer pain demonstrate accelerated brain aging compared with healthy control subjects. The predicted brain age of 59 patients with chronic pain (mean chronological age ± SD: 53.0 ± 9.0 years; 43 women) and 60 pain-free healthy controls (52.6 ± 9.0 years; 44 women) was determined using the software brainageR . This software segments the individual T1-weighted structural MR images into gray and white matter and compares gray and white matter images with a large (n = 2001) training set of structural images, using machine learning. Finally, brain age delta, which is the predicted brain age minus chronological age, was calculated and compared across groups. This study provided no evidence for the hypothesis that chronic pain is associated with accelerated brain aging (Welch t test, P = 0.74, Cohen's d = 0.061). A Bayesian independent-samples t test indicated moderate evidence in favor of the null hypothesis (BF01 = 4.875, ie, group means were equal). Our results provide indirect support for recent models of pain-related changes of brain structure, brain function, and cognitive functions. These models postulate network-specific maladaptive plasticity, rather than widespread or global neural degeneration. Abstract : In patients with chronic noncancer pain, no evidence for accelerated brain aging was found.